Arrangements for Notary Leave in Urgent Circumstances According to the Notary Office Act - UTAMI, I Dewa Ayu Listari; DHARSANA, I Made Pria; SUKANDIA, I Nyoman (Indonesia Strategic Sustainability, 2023)
Purpose:What is the mechanism for arranging the Notary's leave by the Notary's family in an urgent situation? 2. What are the legal consequences of a Notary's leave in an urgent situation on the performance of the position of a Notary based on the Notary Office Law?Methodology:The method chosen for this research is Notary Concept, Substitute Notary Concept, Supervisory Board Concept, Urgent Concept, and Legal Consequences Concept.Findings:The results of the study show that Article 28 of the Law on the Position of a Notary Public shows a blurring of the norms of urgent criteria and only provides a limited and brief explanation, that is, a husband/wife or a straight line from a Notary can submit a request for leave to the Supervisory Board as stated in Article 27 paragraph ( 2), and an urgent situation there are many thoughts of multiple interpretations giving rise to a lack of legal certainty, there is a need for more detailed guidelines or rules regarding Notary leave in urgent circumstances so that it can be carried out following the policy of the Notary Supervisory Board.Implication:The government needs to pay attention to the causes and effects that occur in the regulations that apply at this time so that requests for leave can be implemented in urgent situations so that legal institutions can carry out their duties according to existing law.